Implementation of Progressive Islamic Education from KH. Ahmad Dahlan's Emancipation Perspective in Progressive Islamic Education - Samsuriadi, Samsuriadi; Rama, Bahaking; Malli, Rusli; Mawardi, Amirah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
This research will examine KH. Ahmad Dahlan's thoughts on progressive Islamic education, including the development of religious education. This research uses a qualitative approach with literature analysis to examine various works and thoughts of KH Ahmad Dahlan. The research findings are that KH Ahmad Dahlan's thoughts on progressive Islamic education emphasize the development of socio-emotional, intellectual, moral, and creative potential. The concept of interfaith education that he promoted education does not discriminate against religion, allowing Muhammadiyah schools to accept students from various religious backgrounds. In addition, the implementation of KH. Ahmad Dahlan's thought leads three main concepts: humanization, liberalization, and emancipation perspectives. The humanization perspective emphasizes gender equality in education, the liberalization perspective on awareness of social reality and local culture, and the emancipation perspective on individual liberation from stagnant thinking.